IL-17 Inhibits Oligodendrocyte Progenitor Cell Proliferation and Differentiation by Increasing K+ Channel Kv1.3 - Liu, Han; Yang, Xueke; Yang, Jing; Yuan, Yanpeng; Wang, Yanlin; Zhang, Rui; Xiong, Huangui; Xu, Yuming (Frontiers in Cellular Neuroscience, 2021)
Interleukin 17 (IL-17) is a signature cytokine of Th17 cells. IL-17 level is significantly increased in inflammatory conditions of the CNS, including but not limited to post-stroke and multiple sclerosis. IL-17 has been detected direct toxicity on oligodendrocyte (Ol) lineage cells and inhibition on oligodendrocyte progenitor cell (OPC) differentiation, and thus promotes myelin damage. The cellular mechanism of IL-17 in CNS inflammatory diseases remains obscure. Voltage-gated K+ (Kv) channel 1.3 is the predominant Kv channel in Ol and potentially involved in Ol function and cell cycle regulation. Kv1.3 of T cells involves in immunomodulation of inflammatory progression, but the role of Ol Kv1.3 in inflammation-related pathogenesis has not been fully investigated. We hypothesized that IL-17 induces myelin injury through Kv1.3 activation. To test the hypothesis, we studied the involvement of OPC/Ol Kv1.3 in IL-17-induced Ol/myelin injury in vitro and in vivo. Kv1.3 currents and channel expression gradually decreased during the OPC development. Application of IL-17 to OPC culture increased Kv1.3 expression, leading to a decrease of AKT activation, inhibition of proliferation and myelin basic protein reduction, which were prevented by a specific Kv1.3 blocker 5-(4-phenoxybutoxy) psoralen. IL-17-caused myelin injury was validated in LPC-induced demyelination mouse model, particularly in corpus callosum, which was also mitigated by aforementioned Kv1.3 antagonist. IL-17 altered Kv1.3 expression and resultant inhibitory effects on OPC proliferation and differentiation may by interrupting AKT phosphorylating activation. Taken together, our results suggested that IL-17 impairs remyelination and promotes myelin damage by Kv1.3-mediated Ol/myelin injury. Thus, blockade of Kv1.3 as a potential therapeutic strategy for inflammatory CNS disease may partially attribute to the direct protection on OPC proliferation and differentiation other than immunomodulation.